Secondary cleft palate correction with 3D-printed thermoplastic polyurethane film – a case report - Giovanna Carolina Rothert de Oliveira; Rafael Ricardo Huppes; Ivan Torres Gregorio da Silva (Acta Scientiarum. Animal Sciences, 2024)
Cleft palate is an oronasal communication that can affect the area comprehending the lips and the soft palate. Its clinical signs vary depending on the degree of the defect and the age of the animal, ranging from nasal secretion, coughing, sneezing, halitosis, respiratory difficulty, aspiration pneumonia, and loss of body condition. Its diagnosis is based on inspection of the oral cavity and imaging tests. Palatal defects must be surgically corrected as quickly as possible, using mucosal flaps, grafts, or implants. A desire to evolve alternative treatments for cleft palates drives the search for ways to manufacture customized pieces. 3D printing and biomaterials have enhanced in detail and applicability; combined with design tools and imaging exams, they allow for the making of precise implants and anatomical models for the planning and execution of surgical procedures. This report describes the case of a female, mixed-breed feline treated at a veterinary clinic; it was diagnosed with secondary cleft palate, had a history of falling, and underwent previous palatoplasties with recurrence. A surgical reintervention was performed to implant a 3D-printed TPU film to close its secondary cleft palate.